Intraoperative Blood flow Rate as a Predictor for Maturity of Radiocephalic Arteriovenous Fistula - Pratama, Dedy; Darwis, Patrianef; Yang, Andrew Jackson (The New Ropanasuri Journal of Surgery, 2019)
Introduction. Arteriovenous fistula (AVF) is the best access for hemodialysis. The failure of arteriovenous fistula maturation is currently a major problem faced today. This study aims to assess whether an intraoperative blood flow rate measured with Doppler ultrasound can be a predictor of the maturity ofradiocephalic AVF. Method. Subjects were patients to be made radiocephalic AVFwith USG mapping according to the standard. Shortly after, the anastomosis blood flow rate was measured with a linear probe Doppler ultrasound. This study used a cross-sectional analytic design to obtain radiocephalic AVF maturation relationship with intraoperative blood flow rate. Results. Radiocephalic AVF (n = 71) in 71 patients were made and evaluated in 6 weeks. The mean intraoperative blood flow rate in mature fistulas was significantly higher than those which did not mature (201.85 and 141.96 mL/min; p 165.5 mL/min has a good predictor value for radiocephalic AVF maturation. Thus, it can be used as a reference to determine whether the surgeon needs for further assessment and revision intraoperatively, which in turn is expected to decrease the maturation failure rate of arteriovenous fistula.